Experimental Studies on the Reactive Thrust of the Mobile Robot of Arbitrary Orientation - Mikhail Polishchuk; Mikhail Tkach; Igor Parkhomey; Juliy Boiko; Oleksander Eromenko (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
The problem of creating mobile robots of arbitrary orientation in the technological space is to ensure reliable retention of robots on the surface of any orientation. Therefore, well-known experimental studies are mainly devoted to the creation of systems for coupling the robot to the surface along which it moves. The purpose of this study is to create a device for compensating the gravitational load of a mobile robot. The article contains the results of experimental testing of a fundamentally new approach to counteract the gravitational load of a mobile robot, namely, the expediency of equipping the robot with a source of reactive thrust of a non-chemical origin. A pneumatic generator of aerodynamic lift is proposed as such a source. Such a force partially compensates or completely overcomes the gravitational load, while not allowing the transformation of a mobile robot into an aircraft. The specified condition is necessary to perform contact power technological operations in the maintenance of various industrial facilities. In other words, the thrust force should not exceed the adhesion forces of the mobile robot to the displacement surface. As a research method, a full factorial experiment of the operation of a jet thrust generator was used, which is a new way to increase the reliability of holding the robot on an arbitrary surface. The article describes the methodology and description of the full factorial experiment with varying independent factors at two extreme levels. As a result, an experimental solution to the problem of finding the quasi-optimal values of the aerodynamic lifting force depending on the parameters of the jet thrust generator is obtained. As a result, the combination of a new robot design with the results of experimental studies confirms the feasibility of using a pneumatic jet thrust generator as a means of increasing the reliability of holding mobile robots on an arbitrary orientation surface in the technological space.